2016
DOI: 10.1177/0170840616640845
|View full text |Cite
|
Sign up to set email alerts
|

Knots in the Discourse of Innovation: Investigating Multiple Tensions in a Reacquired Spin-off

Abstract: We examine the case of a corporate spin-off, in which its reacquisition by the parent firm radically changed its structure and culture. Employing a discourse lens, we study paradoxical tensions of innovation as key members "talk into being" the paradoxical circumstances of their environment. From our analysis, we develop the concept of tensional "knots," discursive formulations in which members construct tensions, not only as co-occurring, but as Gordian (inseparable) entanglements of interdependence. Knotted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
208
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(217 citation statements)
references
References 67 publications
(82 reference statements)
6
208
3
Order By: Relevance
“…These nested tensions can create ‘tensional knots’ that can amplify the effects of tensions triggered from the environment (Sheep et al . ).…”
Section: Managers’ Experiences Of Tensions Between Intuition and Analmentioning
confidence: 97%
See 1 more Smart Citation
“…These nested tensions can create ‘tensional knots’ that can amplify the effects of tensions triggered from the environment (Sheep et al . ).…”
Section: Managers’ Experiences Of Tensions Between Intuition and Analmentioning
confidence: 97%
“…These nested tensions can create tensional knots that can amplify the effects of tensions triggered from the environment (Sheep et al . ). This further suggests that examinations into the way managers respond to paradoxes should also include how they respond to the interplay between environmentally derived tensions and any tensions embedded within their own thinking and decision‐making process.…”
Section: Paradox and Dual Process As ‘Nested’ Theories: A Proposed Inmentioning
confidence: 97%
“…One example of research that explicitly adheres to this logic can be found in the work by Sheep et al . (). Inherently addressing the theoretical debate regarding the discourse of innovation, the authors hinge on established paradox theory to advance new levels of understanding in their field of inquiry.…”
Section: Results: Setting Out a Typology Of Contributing Through Paradoxmentioning
confidence: 97%
“…; Jay ; Kodama ; Sheep et al . ; Tse ), organizational interaction (e.g. Le Roy and Fernandez ; Stadtler and Van Wassenhove ), change management (e.g.…”
Section: Results: Setting Out a Typology Of Contributing Through Paradoxmentioning
confidence: 99%
See 1 more Smart Citation